The Correlation Between Indicators of Obesity with Age at Menarche at Elementary School Female Students - Retnowati, Sri; Wiboworini, Budiyanti; Kusumawati, Ratna (Nexus Kedokteran Komunitas, 2015)
Background: Menarche is the first menstrual period in woman reproduction cycle. Recent studies show that the age at menarche is declining. Decline in age at menarche is correlated with obesity. This study aimed to identify the correlation between indicators of obesity with the age at menarche in elementary school students. Method: This was an analytical observational study with cross sectional approach. The subjects of this study were 58 female students of 5th-6th grade at SD Muhammadiyah 1 Surakarta and SD Kristen Manahan (elementary school) that taken by purposive sampling. Indicators of obesity (BMI, waist circumference, waist hip ratio) were measured by anthropometric. Age atÂ  menarche was assessed by using questionnaire. The correlation between indicators of obesity with age at menarche had been analyzed by Spearman correlation test. Result: Spearman correlation test showed that there was no significant correlation between indicators of obesity (BMI, waist circumference, waist hip ratio) with age at menarche with result p=0.650; p=0.894; p=0.829. Spearman correlation test showed that there was no significant correlation between economic and motherâs age at menarche with respondentâs age at menarche (p=0.056 and p=0.087). Conclusion: There is no significant correlation between indicators of obesity with age at menarche in elementary school students. Keywords: indicator of obesity, BMI, waist circumference, waist hip ratio, age at menarche Â